Patients' reasons for weight loss and their relations to clinical weight loss outcomes in a comprehensive lifestyle intervention - Leah Boepple; Ian Cero; Ryan J. Marek; Sandra Coulon; Janet A. Lydecker; Joshua D. Brown; Robert Malcolm; Patrick M. O'Neil (Wiley, 2019)
Summary Objective Research suggests that individuals seeking weight loss treatment do so for a variety of reasons. Limited work has explored relations of reasons for weight loss to patient characteristics or to weight loss outcomes. The current study examined these relations. Methods The sample consisted of 588 patients in a 15‐week fee‐for‐service weight loss programme. Prior to the intervention, patients completed questionnaires including items on reasons for weight loss, demographic characteristics, and a variety of weight‐based characteristics. Patients' weight change outcomes were expressed as percent weight loss and also categorized into one of three previously described weight loss trajectories. Results The results of chi‐squared and t‐test analyses suggested that endorsement of health concerns, mobility concerns, or another person's recommendation was associated with higher body mass index (BMI) and older age. These reasons were more likely to be endorsed by White patients than Black patients and by male patients than female patients. Endorsement of doctor recommendation was more likely to be seen among Black patients than White patients. There was no significant relation of any weight loss reason with weight loss outcome. Conclusions While certain reasons for weight loss were more often cited by certain patient groups, no specific reason predicted a better or worse outcome.